Rethinking participation in global governance: voice and influence after stakeholder reforms in global finance and health - Pauwelyn, Joost; Maggetti, Martino; Büthe, Tim; Berman, Ayelet (Law and global governance series, 2022)
This addition to the Law and Global Governance Series examines participation of stakeholders in treaty-based intergovernmental organizations. Readers are offered a comprehensive account of what has been done to facilitate the participation of previously neglected stakeholders.